The Impact of Student Stress Management on Their Ability to Learn Effectively is Discussed in Covid 19 (International Journal of Food and Nutritional Sciences, 2022)
Due to the abundance of factors that operate as stress catalysts in modern society, stress has become an essential component of daily living. Around the world, Covid-19 has caused enormous distress. Stress affects children of all ages increasingly, and it is not only restricted to adults. Since parents don't have enough time to adequately care for their children, stress management is actually very challenging. Most people have the belief that stress may only result from a sad event, but in reality, stress can also be brought on by a positive experience. There are a variety of factors that can lead to stress in a student's life, including a mismatch between the student and the teacher, which can lead to tension and stress. Lack of parental involvement is another factor in attacks on all students. Children typically don't pay attention to their eating habits, which makes them more vulnerable to stress. Insufficient sleep is a frequent cause of stress that affects students worldwide, therefore that is another factor that contributes to stress. It's difficult to predict how well pupils will manage their stress. Most educational institutions provide optional stress management classes to address this terrible problem, but students frequently lack the time to attend. Through this essay, an effort is made to understand how stress affects pupils and the significance of managing it for good learning.